TRANSFORMASI BIMBINGAN DAN KONSELING TRADISIONAL KE MODERN BERBASIS FILSAFAT HINDU DI PASRAMAN KOTA MATARAM - Triati Lestari Salau; Tri Ayu Lestari (Sophia Dharma: Jurnal Filsafat, Agama Hindu, dan Masyarakat, 2026)
This study aims to analyze the transformation of traditional guidance and counseling toward a modern approach based on Hindu philosophy in a traditional Islamic school (pasraman) in Mataram City. The approach used was descriptive qualitative, with data collection techniques through in-depth interviews, observation, and documentation. The results show that guidance and counseling practices in the pasraman are still dominated by traditional approaches that emphasize moral advice and spiritual guidance, but are not yet supported by modern, systematic, individual-needs-based counseling methods. This condition causes guidance services to be unable to fully address the complexity of students' psychological problems in the modern era. The research findings indicate a need for transformation toward a more dialogical, empathetic, and structured counseling model, without abandoning the values of Hindu philosophy as the main foundation. The integration of the concepts of dharma, karma, yoga, and Catur Purusartha with a modern counseling approach results in a holistic guidance model, namely combining psychological and spiritual aspects in one unit. This study provides a new contribution by confirming that Hindu philosophy can be operationalized applicatively in counseling practice, not only as an ethical norm. Thus, the transformation of guidance and counseling based on Hindu philosophy becomes a strategic solution in shaping students' character and psychological balance in a sustainable manner.